PENYALAHGUNAAN AMFETAMIN DAN DAMPAK PENGGUNA TERHADAP KESEHATAN DAN SOSIAL : LITERATURE REVIEW - Bunga Nur Annisa; Indah Laily Hilmi; Salman Salman (Jurnal Penelitian Farmasi & Herbal, 2022)
Drug abuse is defined as the use of one or more types of drugs without medical regulations or not according to indications so that it has various side effects, including physical, psychological, and social dysfunction. One of the drugs that are often used by the public is amphetamine because amphetamine causes euphoria and a sense of calm (psychotropic group). Hence, the purpose of this literature review is to provide an overview and the most recent information regarding the effects of amphetamine use. The method for this literature analysis is by evaluating references from Science Direct, PubMed, and Google Scholar, with a publication restriction of the previous 10 years. Based on the relevant literature, amphetamine misuse has diverse impacts on its users. Drug abuse has psychological and physical effects on adolescents (students) to adults and affects a person's social interactions.